2013
DOI: 10.12691/ajmbr-1-3-1
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dysfunctions as Self-Reported by Diabetic- Type-2 Men: An Andrology Clinic-Based Study in Alexandria, Egypt

Abstract: Objectives: To document the prevalence of self-reported sexual dysfunctions (SDs) in diabetic type 2 (DM2) men attending the andrology clinic in the Alexandria University hospital. Methods: A retrospective analysis of clinical case records of 276 consecutive DM2 and 100 consecutive non-diabetic (controls) men who reported SDs directly to the andrology clinic was done. Results: The majority of the patients and controls had light manual occupation, low education level and no history of smoking. No patient report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
(62 reference statements)
0
7
4
Order By: Relevance
“…PE was the second most common SD selfreported by 38.9% study participants either as a single SD or in combination with other SDs. It was higher than that reported by Shaikh et al 27 (20%) in the same community while Salama 14 reported 22.4% prevalence of PE but this difference can possibly be due to change in the sample size and methodology. However, it was little lower than that revealed by El-Sakka 32 (40.2%) and Malavige et al 28 (40.2%).…”
Section: Discussioncontrasting
confidence: 65%
“…PE was the second most common SD selfreported by 38.9% study participants either as a single SD or in combination with other SDs. It was higher than that reported by Shaikh et al 27 (20%) in the same community while Salama 14 reported 22.4% prevalence of PE but this difference can possibly be due to change in the sample size and methodology. However, it was little lower than that revealed by El-Sakka 32 (40.2%) and Malavige et al 28 (40.2%).…”
Section: Discussioncontrasting
confidence: 65%
“…There have been few attempts to study the prevalence of DE and AE in DM. While one study showed 0% prevalence among a series of 54 diabetes patients[ 129 ], another research demonstrated self-reported absent ejaculation and DE in 7.2 % and 0.36 % respectively among a total series of 276 diabetes patients[ 130 ]. However, sporadic cases were reported in literature either in the context of fertility evaluation[ 110 , 131 ] or as a sexual complaint[ 132 ].…”
Section: Diabetes-related Ejaculatory Dysfunctionsmentioning
confidence: 99%
“…According to the National Diabetes Information Clearinghouse (2008), that as many as 20-75% of patients with diabetes mellitus sexual dysfunction (5). Sexual dysfunction in patients with diabetes will experience libido disorders, ejaculation disorders, and erectile dysfunction (6). The frequency of erectile dysfunction in patients with diabetes will increase by four times as much at the age of 40-70 years (7).…”
Section: Introductionmentioning
confidence: 99%